2006
DOI: 10.1002/ijc.22332
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: In vitro and in vivo molecular evidence of genistein action in augmenting the efficacy of cisplatin in pancreatic cancer

Abstract: We recently reported the potential of genistein in augmenting gemcitabine-induced killing of pancreatic cancer (Banerjee, S. et al., Cancer Research 2005;65:9064-72). Since cis-diaminedichloroplatinum (II) (cisplatin) is widely used against solid tumors, we further investigated whether genistein pretreatment could be used as a novel strategy for cisplatin-induced killing of pancreatic cancer cells in vitro and enhanced antitumor activity in vivo. Our in vitro results showed that pretreatment of cells with gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 43 publications
7
61
0
Order By: Relevance
“…We also found that piperlongumine downregulated the constitutive activation of NF-kB in pancreatic cancer cell lines. These results on downregulation of NF-kB activation by piperlongumine are consistent with previous reports that piperlongumine inhibited activation of NF-kB in other cancer cell lines (30,39) and with reports that resveratrol (45), genistein (46), dihydroartemisinin (44), zyflamend (47), g-tocotrienol (48), curcumin (49), shikonin (9), and 3,3 0 -Diindolylmethane (50), all present within piperlongumine, are associated with NF-kB inactivation.…”
Section: Discussionsupporting
confidence: 92%
“…We also found that piperlongumine downregulated the constitutive activation of NF-kB in pancreatic cancer cell lines. These results on downregulation of NF-kB activation by piperlongumine are consistent with previous reports that piperlongumine inhibited activation of NF-kB in other cancer cell lines (30,39) and with reports that resveratrol (45), genistein (46), dihydroartemisinin (44), zyflamend (47), g-tocotrienol (48), curcumin (49), shikonin (9), and 3,3 0 -Diindolylmethane (50), all present within piperlongumine, are associated with NF-kB inactivation.…”
Section: Discussionsupporting
confidence: 92%
“…This later result might be surprising, since genistein was earlier reported to enhance the toxicity of cisplatin in other tumor cell types. 22,47 Nonetheless, the inability of genistein to increase apoptosis induction by drugs other than ATO in U937 cells seems to be consistent with its failure to inhibit Akt phosphorylation and NF-jB activation, since Akt and NF-jB are protective factors against multiple stressing treatments. Of note, our results only indicate that Akt and NF-jB do not play a main regulatory role under the present experimental conditions, but do not prejudge the capacity of genistein to modulate Akt/NF-jB in leukemia cells in other conditions, nor necessarily contradicts earlier observations in other cell types.…”
Section: Discussionmentioning
confidence: 87%
“…The constitutive activation of NF-ÎșB is believed to promote inhibition of apoptosis and resistance to chemotherapy (Arlt and Schafer, 2002;Holocomb et al, 2008;Liptay et al, 2003). This notion is further supported by the fact that inactivation of NF-ÎșB sensitizes cancer cells to conventional chemotherapies (Banerjee et al, 2005;Banerjee et al, 2007). Therefore, treating pancreatic cancer with NF-ÎșB inhibitors can improve the outcomes of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have demonstrated that inhibition of spontaneous NF-ÎșB activation can potentiate the anticancer effect of various chemotherapeutic agents (Banerjee et al, 2007). Thus, we treated the cell with evodiamine in the presence of SN50, a specific NFÎșBp65 inhibitor and cell death was measured by live/ dead assay and apoptosis assay.…”
Section: Discussionmentioning
confidence: 99%